Estrogens Reduce Plasma Histidine-rich Glycoprotein (HRG) Levels in a Dose-dependent Way - Hennis, B C; Boomsma, D I; Fijnvandraat, K; Leuven, J A Gevers; Peters, M; Kluft, C (Thrombosis and Haemostasis, 1995)
Plasma levels of histidine-rich glycoprotein (HRG) were investigated in three groups of women receiving a different dose of estrogens. First, the effect of low-dose estrogen was studied in a group of 83 postmenopausal women who were treated with 0.625 mg conjugated estrogens (CE). No significant change from baseline levels was found at the end of cycle 3 and cycle 13. Secondly, in 15 mothers and 23 daughters using oral contraceptives (OC) containing 30-50 fig ethinyl estradiol (EE) daily the mean HRG level was 14% and 24% lower than in a group of 144 mothers and 134 daughters not taking oral contraceptives, respectively (p < 0.05). Finally, in 11 excessively tall prepuberal girls who received 300 μg EE daily to reduce their final height the mean plasma HRG levels were decreased by 68% (p < 0.005). The effect of proges- togens administered during low-dose and high-dose estrogen therapy appeared to be minor.The results from these three studies indicate that estrogens reduce plasma HRG levels in a dose-dependent way.